Efektifitas Pembelajaran Kontekstual Model Pengajaran Berbasis Masalah Dalam Meningkatkan Prestasi dan Penguasaan Materi Pelajaran IPA Pada Siswa Kelas IV - Jumisnar Jumisnar (Yayasan Darussalam Bengkulu, 2020)
To be able to learn science learning materials properly, we need to listen, see, ask questions about it, and discuss it with others. In addition, students also need to do it, which is describing things in their own way, showing examples, trying to practice skills and doing assignments that demand the knowledge they have gained. This study uses classroom action research of three cycles. Each cycle consists of four stages, namely design, activity and observation, reflection, and revision. The target of this research is the fourth grade students of SDN 03 Mukomuko City. The data obtained in the form of learning outcomes from formative tests and observation sheets of teaching and learning activities. The results showed that student achievement increased from cycle I to cycle III namely, cycle I (64.00%), cycle II (76.00%), cycle III (88.00%). The conclusion of this study is that problem-based contextual learning can positively influence the learning outcomes of fourth grade students of SDN 03 Mukomuko City. This learning model can be used as an alternative in science learning .